2014
DOI: 10.1111/1475-6773.12188
|View full text |Cite
|
Sign up to set email alerts
|

Patient Selection and Volume in the Era Surrounding Implementation of Medicare Conditions of Participation for Transplant Programs

Abstract: Although trends in aggregate risk of 1-year kidney graft loss do not indicate that the introduction of the CoPs has systematically reduced opportunities for marginal candidates or that there has been a systematic shift away from utilization of higher risk deceased donor kidneys, total volume and expanded criteria donor utilization decreased overall among programs with ongoing noncompliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 21 publications
2
37
0
Order By: Relevance
“…Centers flagged according to CMS conditions of participation decreased their overall transplant rates and to an even greater degree acceptance of ECD kidneys during a period of overall transplant growth at remaining centers. 20,21 While, these survival metrics are risk-adjusted by the SRTR according to recipient age and donor KDPI, concerns regarding the adequacy of this risk adjustment have been ongoing and pervasive. As such, proposals to exclude KDPI >85% transplants from transplant center regulatory metrics or to measure these graft outcomes separately have been suggested to encourage utilization of the organs nationally.…”
Section: Discussionmentioning
confidence: 99%
“…Centers flagged according to CMS conditions of participation decreased their overall transplant rates and to an even greater degree acceptance of ECD kidneys during a period of overall transplant growth at remaining centers. 20,21 While, these survival metrics are risk-adjusted by the SRTR according to recipient age and donor KDPI, concerns regarding the adequacy of this risk adjustment have been ongoing and pervasive. As such, proposals to exclude KDPI >85% transplants from transplant center regulatory metrics or to measure these graft outcomes separately have been suggested to encourage utilization of the organs nationally.…”
Section: Discussionmentioning
confidence: 99%
“…White et al demonstrated that transplant volume declined 38% among programs with ongoing non-compliance with CMS CoP compared with a 6% increase in those programs remaining in compliance. [13] Schold et al identified a mean decline of 22.4 transplants annually in centers with a of LP PSR compared with an average 7.8 transplant increase annually for other centers during the same time period. [14] Of concern, almost a quarter of kidney transplant centers had LP report during this period.…”
Section: Unitended Consequences and Disincentivesmentioning
confidence: 99%
“…White et al showed evidence that programs with ongoing LP had a higher burden of risk due to recipient factors. [13] It is not surprising then, that one strategy employed by transplant centers fearful of regulatory trouble is more restrictive listing and transplant practices. In a survey of individuals in transplant administrative roles, 81% of centers with LP evaluations in the past 3 years had increased candidate selection criteria, and 94% of centers with LP evaluations and lost contracts had increased their criteria.…”
Section: Unitended Consequences and Disincentivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have found a decrease in transplant volume among centers “flagged” for low performance after the CMS Conditions of Participation were introduced, reducing access to transplantation for patients in the area . Furthermore, concern about post‐transplant outcome metrics included in report cards has been cited as a deterrent to providers’ willingness to accept organs from higher risk donors . Although receiving a transplant, even from an organ at increased risk of disease transmission (IRD), has survival benefit compared to remaining on dialysis, IRD organs are more likely to be discarded than non‐IRD organs .…”
Section: Introductionmentioning
confidence: 99%